Effects of an intervention combining physical activity and components of Amygdala and Insula Retraining (AIR) on sleep and working memory among older male adults - Monireh Asadi Ghaleni; Forouzan Fattahi Masrour; Narjes Saryar; Alexandra J. Bratty; Ebrahim Norouzi; Matheus Santos de Sousa Fernandes; Georgian Badicu (AIMS Neuroscience)
BackgroundOlder individuals are at a particular risk of sleep disorders, a loss of cognitive and emotional control, and a poor quality of life. Pharmaceutical therapy for these conditions is commonplace but has not been particularly effective, and relatively little research exists for their treatment using non-pharmacological approaches. The effectiveness of Physical Activity plus selected components of Amygdala and Insula Retraining (PAAIR) was tested to improve sleep quality, depression, working memory, and emotion regulation among older males.MethodsThis was a parallel, randomized control trial. The study was conducted in-person among 40 older Iranian men (Mage: 65.78, SD = 2.41). The participants were randomly assigned with equal allocation to either the PAAIR or a control condition. Both interventions were conducted in-person over 12 weeks. The participants met twice weekly for 45-minute sessions at a local elderly training and rehabilitation center. All participants completed measurements for sleep quality, depressive symptoms, working memory, and emotion regulation at baseline, 12 weeks (immediately after the intervention), and 8 weeks later.ResultsAmong the 36 individuals who finished the study, their sleep quality, working memory, and emotion regulation improved, and their depressive symptoms were reduced from baseline to 12 weeks (post-intervention) and 8 weeks later; these effects were seen even more so for the PAAIR group compared to the control group, with large to extremely large effect sizes.ConclusionThe findings suggest that PAAIR has the potential to enhance sleep quality, cognitive function, and emotion regulation and reduce depressive symptoms among older men, thus contributing to their quality of life and mental health.